Experimental transmission of a Herpes-like virus to axenic larvae of Pacific oyster, Crassostrea gigas - Le Deuff, Rose-marie; Nicolas, Jean-louis; Renault, Tristan; Cochennec, Nathalie (EAFP, 1994)
A herpes-like virus which was associated with mortalities amongst hatchery-reared larvae of Pacific oysters, Crassostrea gigas. was observed for the first time in France during the summer 1991 (Nicolas et al. 1992). Since this first report, we have noted further outbreaks of the disease in the summers of 1992 and 1993 in hatcheries on the western coasts of France in which a similar virus was associated with moribund larvae. Moreover, in the summer 1991, Hine et al. (1992) described a herpes-like virus responsible for larval mortality of hatchery reared C. gigas, in New Zealand. Ail these viruses are c10sely related with respect to their size and morphology and to their apparent cellular tropism for fibroblastic cells.